2019
DOI: 10.1021/acsami.9b03449
|View full text |Cite
|
Sign up to set email alerts
|

DNA-Based Nanomedicine with Targeting and Enhancement of Therapeutic Efficacy of Breast Cancer Cells

Abstract: Recently, a DNA tetrahedron has been reported to be a novel nanomedicine and promising drug vector because of its compactness, biocompatibility, biosafety, and editability. Here, we modified the DNA tetrahedron with a DNA aptamer (AS1411) as a DNA-based delivery system, which could bind to nucleolin for its cancer cell selectivity. Nucleolin is a specific biomarker protein overexpressed on membranes of malignant cancer cells and its deregulation is implicated in cell proliferation. The antimetabolite drug 5-fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
74
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 88 publications
(78 citation statements)
references
References 52 publications
0
74
0
Order By: Relevance
“…Previous studies have indicated that tFNAs can promote the proliferation of various cell types. 24 27 , 29 , 34 , 35 Therefore, in this research, we aimed to determine whether this type of effect also existed in HaCaT and HSF cells. CCK-8 assays were used to examine cell proliferation, while cell-cycle assays were used to analyze changes in the number of cells at each stage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have indicated that tFNAs can promote the proliferation of various cell types. 24 27 , 29 , 34 , 35 Therefore, in this research, we aimed to determine whether this type of effect also existed in HaCaT and HSF cells. CCK-8 assays were used to examine cell proliferation, while cell-cycle assays were used to analyze changes in the number of cells at each stage.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in previous studies, tFNAs are able to promote cell migration. 27 29 , 35 Scratch experiments are widely performed to investigate cell migration in vitro, but there are still factors that can interfere with these outcomes. In this study, to minimize variability, all scratches were made by the same person.…”
Section: Discussionmentioning
confidence: 99%
“…B, AS1411 aptamer‐modified TDN for selective 5‐fluorouracil (5‐FU) delivery to breast cancer cells. Reproduced with permission 52 . C, Methylene blue (MB)‐loaded TDN for in vitro and in vivo photodynamic therapy.…”
Section: Applications As Delivery Vehicles In Cancer Therapymentioning
confidence: 99%
“…The same group also reported the use of AS1411‐aptamer‐modified TDN to deliver the antimetabolite 5‐fluorouracil to specific breast cancer cells (Figure 3B). 51 The modified TDN showed the effect on cell cycle and apoptotic genes and proteins. Moreover, Chen and coworkers developed the anticancer metal complex, [Ir(ppy) 2 phen] + PF 6 (Ir)‐loaded TDN, to inhibit vascular mimicry (VM) formation, which enhances tumor migration and metastasis in glioma 52 .…”
Section: Applications As Delivery Vehicles In Cancer Therapymentioning
confidence: 99%
“…Chemotherapy drugs usually cause apoptosis of cancer cells via generating a large number of reactive oxygen species (ROS) (Zhan et al, 2019). Therefore, the ROS generation in HeLa cells was examined by fluorescence in this study.…”
Section: Rgdfc-se@sirna Induces Mitochondrial Dysfunction Through Rosmentioning
confidence: 99%